Pengaruh Orientasi Pasar dan Citra terhadap Kepuasan Mahasiswa dan Implikasinya terhadap Loyalitas Mahasiswa - Mulyono, Herry (Jurnal Aplikasi Manajemen, 2016)
The universities are currently facing many challenges as an institution of higher education providers, especially private universities to compete for students, maintaining the values of academic that produce graduates who can compete in creating jobs, and enter the workforce. This study aimed to analyze the effectof market orientation and image to the student satisfaction, and the implication to the student loyalty. Data collection was taken from students in Jambi as many as 200 samples with analytical methods WarpPLS Structural Equation Model 3.0. The result showed that all of hypothesis has positive and significant impact, which Market Orientation greatest effect.